Pengukuran Hubungan Antara Kinerja Perawat dan Faktor Yang Berpengaruh di Rumah Sakit Prikasih Jakarta Selatan - Siti Utami Dewi (Jurnal Persada Husada Indonesia, 2018)
Nurse as one of the health workers in hospitals plays an important role in achieving the goal of health development. The success of health care depends on the participation of nurses in delivering quality care for patients. The purpose of this study was to determine the direct and indirect influence as well as the amount of work environment, job training, and employability and work discipline on the performance of nurses in Prikasih Hospital South Jakarta Year 2016. The method used in this study is quantitative approach that use cross-sectional design. Samples used as many as 80 nurses as respondents. The analytical method used was Structural Equation Model (SEM) using SmartPLS 2.0 and SPSS 20. Results of hypothesis testing by Structural Equation Model (SEM) using smartPLS produce research findings that performance of nurses variable at Hospital South Jakarta Prikasih influenced by work environment (19.57%), job training (22.67%), ability to work (20.51%) and discipline (12.01%) The total direct effect was 74.8%. While the indirect effect of work environment (1.046%), job training (0.198%), and ability to work (0.209%). Therefore the total direct and indirect influences were 76.2%. Model analysis results can explain 99.78% diversity of data and able to assess the phenomenon used in the study, while the 0.22% described other components that do not exist in this study. The result showed a greater effect namely vocational training because training as a form of development capabilities and skills of nurses. The research suggest nurses should be train cross-sectionally in order to complement and helping each other, therefore it could enhance teamwork among leaders, nurses and their colleagues to achieve hospital goals.